Roland Barthes’ Semiotic Analysis of the Meaning of Al-Mā’ in QS. Al- Anbiyā’ [21]: 30 - Luqman Hakim (Jurnal test, 2026)
Water in the Qur’an occupies a very important position, not only as a physical element but also as having sacred spiritual and theological dimensions. Amid the global ecological crisis and advances in reproductive bioethics, the meaning of water is often reduced to a mere economic commodity or a passive biological object. This study aims to deconstruct the shift in the meaning of al-mā’ in QS. Al-Anbiyā’ [21]: 30 using Roland Barthes’ semiotics to reveal the layers of meaning contained within literal, symbolic, and ideological that are relevant to the contemporary context. The method used in this research is qualitative-hermeneutic, focusing on Roland Barthes’ semiotic analysis technique which is capable of dissecting the text into three layers: denotation, connotation, and myth. The results show that at the denotation level, al-mā’ signifies water as a vital element of life and sperm as the biological origin of humans. At the connotation level, water transforms into a symbol of God’s grace, a sign of cosmic origins, spiritual purity, and the continuity of generations. At the myth level, al-mā’ represents the ideology of biological sustainability, ecology, and “green theology”. It also represents the responsibility of humans as khalifah (stewards) to protect a divine trust. Furthermore, the Qur’an offers a “counter-myth” against a modernity that deadens water and exploits nature. Water is a theological mandate, not merely a limitless commodity to be freely exploited. This research provides a significant contribution by asserting that water conservation is a tawhid (monotheistic) obligation rather than just an ethical choice.